'That's deep bro': Negotiated readings and democratic education in an Australian high school classroom. Issue 6 (2nd November 2021) - Anson, Daniel W. J.
ABSTRACT: This paper presents data from an Australian high school classroom, investigating how students and their teacher negotiate readings of literature in order to arrive at meanings that are valued by subject English, as well as understood by the students. Subject English acts a vital agent for the transmission of both literacy and literary knowledge in English-speaking countries, and students which do not share the cultural and social orientations valued by the subject and its texts have the potential to be disadvantaged. However, I argue that this clash of socio-cultural perspectives may be positively viewed as an advantage for democratic education, as it allows students' critical understanding of their world to be challenged, for teachers to include student perspectives, and for students to be empowered to participate in institutional discourses. Implications for teacher practice and educational theory are discussed.